Microstructure of horizontally continuously cast Stellite rods - Bajželj, Anže; Burja, Jaka (Frontiers in Mechanical Engineering, 2026)
This study investigates the microstructural and phase characteristics of Stellite 6, Stellite 12, and Stellite 21 alloys produced by horizontal continuous casting. The alloys were synthesized from pure metallic elements and ferroalloy (FeW) under an argon atmosphere and solidified in a water-cooled copper mould (Ø3.3 mm–Stellite 6 and Stellite 21, and Ø6.1 mm–Stellite 12), resulting in extremely high cooling rates and fine-grained microstructures. Thermodynamic calculations were performed to predict equilibrium solidification, which was compared with experimental microstructural observations. Optical and scanning electron microscopy (SEM-EDS) analyses revealed Co-rich dendritic grains surrounded by eutectic regions containing carbides of the M7C3, M23C6, and M6C types. X-ray diffraction (XRD) confirmed the presence of an FCC Co matrix without HCP phase formation, attributed to rapid solidification. The volume fraction of carbides increased with carbon content, influencing hardness. Vickers hardness measurements showed that Stellite 6 exhibited the highest hardness (508 HV10), followed by Stellite 12 (470 HV10) and Stellite 21 (345 HV10). The finer grain size and higher carbide fraction in alloys with greater carbon content contributed to enhanced hardness and structural uniformity. These findings demonstrate that horizontal continuous casting enables the production of fine-grained Stellite rods with a homogeneous composition. The cast rods show excellent structural integrity and are well-suited for subsequent hard-facing applications in wear-resistant environments.